Implementing enhanced recovery after surgery. Issue 6 (30th November 2015) - Meacham, Kimberly L.; Odhner, Margaret; Norsen, Lisa H.; Schmidt, Ellen; Rowe, Karess
Abstract : The fast track to recovery discussed in this article optimizes a patient's perioperative course by reducing the stress of surgery, decreasing surgical complications, and accelerating postoperative recovery.